Perancangan dan Implementasi E-Tourism Berbasis Website Pada Dinas Pariwisata Kota Palembang - Aldi Syawal; Kurniawan (JUPITER (Jurnal Penelitian Ilmu dan Teknologi Komputer), 2023)
Tourism is one of the sectors that have the potential to generate income for the Palembang City government. Therefore, various ways have been done by the Palembang City Government to improve the quality of existing tourism, one way to improve the quality of existing tourism is to implement an information system in the field of tourism or better known as E-Tourism. E-Tourism can be a way out for the government to solve tourism development problems and the problem is the lack of information for tourists. With the availability of various aspects of tourism information such as tourist attractions, and events that can be accessed 24 hours a day, it will help tourists in making decisions about tourism travel plans in the city of Palembang. In conducting this research, the system development method used is the Extreme Programming method where the tools used for database design are ERD, table relations, normalization. For structured method planning using DFD system development tools, context diagrams, Flowcharts. While the implementation and software that supports using the PHP programming language with MySQL database. By developing a website regarding the e-tourism information system at the Palembang City tourism office, it is hoped that it can assist in providing information about tourism in the city of Palembang.